Delayed onset of autoreactive antibody production and M2-skewed macrophages contribute to improved survival of TACI deficient MRL-Fas/Lpr mouse - Liu, Lunhua (Sci Rep, 2018)
Anti-B cell activating factor belonging to TNF-family (BAFF) antibody therapy is indicated for the treatment of patients with active systemic lupus erythematosus (SLE). We hypothesized that the BAFF receptor, transmembrane activator and calcium-modulator and cyclophilin interactor (TACI) may be responsible for the generation of antibody secreting plasma cells in SLE. To test this hypothesis, we generated TACI deficient MRL-Fas/Lpr (LPR-TACI−/−) mouse. TACI deficiency resulted in improved survival of MRL-Fas/Lpr mice and delayed production of anti-dsDNA and anti-SAM/RNP antibodies. There was also a delay in the onset of proteinuria and the accumulation of IgG and inflammatory macrophages (Mϕs) in the glomeruli of young LPR-TACI−/− mice compared to wild-type mice. Underscoring the role of TACI in influencing Mϕ phenotype, the transfer of Mϕs from 12-week-old LPR-TACI−/− mice to age-matched sick wild-type animals led to a decrease in proteinuria and improvement in kidney pathology. The fact that, in LPR-TACI−/− mouse a more pronounced delay was in IgM and IgG3 autoreactive antibody isotypes and the kinetics of follicular helper T (Tfh) cell-development was comparable between the littermates suggest a role for TACI in T cell-independent autoantibody production in MRL-Fas/Lpr mouse prior to the onset of T cell-dependent antibody production.